Investigating the Relationship Between Problematic Social Media Use and Dark Personality Traits with the Mediating Role of Emotion Regulation Among Adult Instagram Users in Tehran - Jamshidi, Sara; Noferesti, Azam; Farahani, Hojjatollah (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of the present study was to investigate the relationship between problematic social media use and dark personality traits with the mediating role of emotion regulation among adult Instagram users in Tehran. Methods and Materials: The research method was descriptive-correlational and utilized a structural equation modeling approach. The population included all adult Instagram users (aged 18 to 80) in Tehran in the year 2022. The sample consisted of 306 individuals selected through convenience sampling. The questionnaires used in the study were the Mobile Social Networking Addiction Scale by Khajeh Ahmadi et al. (2016), the Dark Personality Traits by Jonason and Webster (2010), Emotion Regulation by Gratz and Roemer (2004), and Self-Compassion by Neff (2003). Data analysis was performed using Structural Equation Modeling and Amos.22 software. Findings: The results showed a significant positive relationship between problematic social media use and dark personality traits (p = .001, β = .523). There was a significant positive relationship between emotion regulation and dark personality traits (p = .001, β = .376). A significant positive relationship existed between problematic social media use and emotion regulation (p = .001, β = .602). Moreover, the indirect path coefficient between problematic social media use and dark personality traits was negative and significant (p = .001, β = -.275). The indirect path coefficient between problematic social media use and dark personality traits through emotion regulation was positive and significant (p = .001, β = .226). Emotion regulation significantly mediated the relationship between problematic social media use and dark personality traits in a positive manner. Conclusion: It can be concluded that emotion regulation is an important component in predicting problematic Instagram use.